ALAT MONITORING TRANSFORMATOR MENGGUNAKAN METODE TRACKING BERBASIS ARDUINO PADA PT. PLN - Supardi Sigit; Fajri Setiawan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2018)
Transformator or often called trafo is one of the electrical devices that can change the level of a voltage, transformator (trafo) plays an important role in the distribution of electricity to the public. In general, electrical devices such as trafo when working can cause heat, if it is left just like that, the temperature that continues to increase can interfere with performance or can even cause the trafo to explode due to excessive heat temperature. To overcome this, the officers of PT. PLN conduct regular checks every month, therefore to lighten the work of officers, a temperature monitoring system and trafo location information is made based on google map. Information on temperature and location statistics can be directly accessed through the smartphone application that is already available.